PyThea: An open-source software package to perform 3D reconstruction of coronal mass ejections and shock waves - Kouloumvakos, Athanasios; Rodríguez-García, Laura; Gieseler, Jan; Price, Daniel J.; Vourlidas, Angelos; Vainio, Rami (Frontiers in Astronomy and Space Sciences, 2022)
PyThea is a newly developed open-source Python software package that provides tools to reconstruct coronal mass ejections (CMEs) and shocks waves in three dimensions, using multi-spacecraft remote-sensing observations. In this article, we introduce PyThea to the scientific community and provide an overview of the main functionality of the core software package and the web application. This package has been fully built in Python, with extensive use of libraries available within this language ecosystem. PyThea package provides a web application that can be used to reconstruct CMEs and shocks waves. The application automatically retrieves and processes remote-sensing observations, and visualizes the imaging data that can be used for the analysis. Thanks to PyThea, the three-dimensional reconstruction of CMEs and shock waves is an easy task, with final products ready for publication. The package provides three widely used geometrical models for the reconstruction of CMEs and shocks, namely, the graduated cylindrical shell (GCS) and an ellipsoid/spheroid model. It also provides tools to process the final fittings and calculate the kinematics. The final fitting products can also be exported and reused at any time. The source code of PyThea package can be found in GitHub and Zenodo under the GNU General Public License v3.0. In this article, we present details for PyThea's python package structure and its core functionality, and we show how this can be used to perform three-dimensional reconstruction of coronal mass ejections and shock waves.